ANALISIS PENGEMBANGAN FITUR APLIKASI MOBILE BANKING PADA BANK XYZ - Nanda Nurisya Merliani; Retno Waluyo (JURNAL REKAYASA INFORMASI, 2022)
Bank XYZ is one of the banks that has developed the use of mobile banking. Along with the development of the use of mobile banking, many competing banks are improving their services and innovating mobile banking features, so that they can become a threat. Bank XYZ must improve competitiveness against competing banks by identifying problems using the SWOT analysis method, then mapping the priority problems using the Eisenhower Matrix method to determine the feature development that can be done so that Bank XYZ can provide better and optimal banking services. From the SWOT and Eisenhower Matrix analysis that has been carried out, recommendations for the development of XYZ Bank mobile banking features are developed, namely the development of promo features equipped with promo categories, authentication of the registration flow to be more organized, and the addition of budget features that regulate customer finances in knowing and managing budget every month.